2020
DOI: 10.1007/s00221-020-05758-2
|View full text |Cite
|
Sign up to set email alerts
|

Balance control is impaired by mental fatigue due to the fulfilment of a continuous cognitive task or by the watching of a documentary

Abstract: The aim of the present study was to evaluate the effects of mental fatigue (MF) induced by a 90-min continuous demanding cognitive task on balance control. Twenty healthy young participants were recruited. They had to perform three postural tasks (on a stable support with eyes open, with eyes closed and on a wobble board) while standing on a force platform before and after watching a documentary in a control condition or carrying out a prolonged continuous demanding cognitive task (AX-continuous performance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…YBT performance did not change as a consequence of mental fatigue or watching a documentary. Hachard et al (2020) 30 also assessed the effects of mental fatigue on balance control with a similar study design, but by using a more sensitive measuring instrument (ie, force plate). They also let participants perform a 90‐minute continuous cognitive task (AX‐continuous performance test) as an intervention and watch a 90‐documentary as a control task, whereas balance control was measured before and after these 90‐minute tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YBT performance did not change as a consequence of mental fatigue or watching a documentary. Hachard et al (2020) 30 also assessed the effects of mental fatigue on balance control with a similar study design, but by using a more sensitive measuring instrument (ie, force plate). They also let participants perform a 90‐minute continuous cognitive task (AX‐continuous performance test) as an intervention and watch a 90‐documentary as a control task, whereas balance control was measured before and after these 90‐minute tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that both mental fatigue and watching a documentary impaired balance control in the three different quiet stance tasks. The authors mainly attributed their results to the deleterious effect of prolonged sitting rather than to impairments in cognitive or attentional resources 30 . For the YBT, one possible explanation might be that the sensitivity of the traditional YBT is insufficient to detect delicate changes in balance control.…”
Section: Discussionmentioning
confidence: 99%
“…Hachard and colleagues observed that unexpectedly, their control condition of watching a documentary had adverse effects on performance in subsequent balance control tests in young, healthy participants (Hachard, Noé, Ceyte, Trajin, & Paillard, 2020). The authors discuss that participants' reduced performance in balance control following the control condition could be due to a deleterious effect of prolonged sitting.…”
Section: Discussionmentioning
confidence: 99%
“…Stratification was performed based on age group, i.e. separately for children (7)(8)(9)(10)(11)(12) years) and adolescents (13-18 years). In each age group, random allocation was performed using a random number table.…”
Section: Interventionmentioning
confidence: 99%
“…Mental fatigue compromises executive control over daily cognitive activities which leads to declined attention and cognitive performance. Reaction, response time and accuracy, decision-making, planning, motivation, and even psychomotor and physical performance are affected by metal fatigue (8,9) .…”
Section: Introductionmentioning
confidence: 99%